2018
DOI: 10.1096/fj.201700605r
|View full text |Cite|
|
Sign up to set email alerts
|

K Ca 2 channel localization and regulation in the axon initial segment

Abstract: Small conductance calcium-activated potassium (K2) channels are expressed throughout the CNS and play a critical role in synaptic and neuronal excitability. K2 channels have a somatodendritic distribution with their highest expression in distal dendrites. It is unclear whether K2 channels are specifically present on the axon initial segment (AIS), the site at which action potentials are initiated in neurons. Through a powerful combination of toxin pharmacology, single-molecule atomic force microscopy, and dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…SK3 channels are found on dendrites and AIS (Abiraman et al, 2018 ). They play a role in AP propagation and regulation of neuronal excitability (Stocker, 2004 ).…”
Section: K + Channelsmentioning
confidence: 99%
“…SK3 channels are found on dendrites and AIS (Abiraman et al, 2018 ). They play a role in AP propagation and regulation of neuronal excitability (Stocker, 2004 ).…”
Section: K + Channelsmentioning
confidence: 99%
“…Furthermore, activating post-synaptic muscarinic acetylcholine receptors enhanced the activity of Cav3.2 in hippocampal granule cells, resulting in Kv7 inhibition and decreased spike threshold [39]. Ca 2+ entry through AIS NMDA receptors during increased activity results in Nav and Kv7 endocytosis [40] and along with other Ca 2+ sources may also activate SK channels recently observed at the AIS of hippocampal neurons [41]. Finally, dopamine can inhibit Cav3 at the AIS of cartwheel cells, lowering excitability and suppressing burst output [42] (Summary in Figure 2b).…”
Section: Neurotransmitter Regulation Of Ais Excitabilitymentioning
confidence: 99%
“…As in other central neurons, like Purkinje cells [ 28 , 36 ], inferior olivary cells [ 37 ], pyramidal neurons [ 30 , 31 , 38 ]], in Golgi cells the dendritic calcium channels played a fundamental role. A variety of Ca channels were located in the dendrites [ 14 ] and AIS [ 23 , 39 ]. The models showed that, in basal dendrites, Cav2.2 channel activation followed the action potential trajectory generating rapid Ca transients.…”
Section: Discussionmentioning
confidence: 99%